(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Pancasila as the main view of life for the people of Indonesia. Teachers have an important role in educating the younger generation to be able to apply the values of Pancasila well. Pancasila not only serves as a guideline for interacting in society, but also as a foundation for building strong character and morals in the younger generation. Through Pancasila education, students are educated to apply these values from the first precept to the last precept in various aspects of life. This research uses a qualitative approach through the literature review method. Literature research uses methods to collect, evaluate, and synthesize data from various sources about the research subject. The data of this research article is sourced from articles published on Google Scholar. The data analysis used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. Studies show that the role of teachers in building Pancasila values has a significant influence on student morale. The teacher is not only a teacher, but also an example to follow and a guide who guides students in the learning process. In creating an educational environment that facilitates the formation of character and morals in accordance with the values of Pancasila, teachers play a very strategic role. The role of teachers in educating the younger generation with the values of Pancasila is important in building a civilized and cultured society.